Value-Driven Management in the Bhagavad Gita: A Framework for Sustainable and Ethical Organizational Practices - Rani Aneja, Lieutenant (Dr.) Suksham; Arya, Akansha; Khari, Abhishek; Teotia, Yashkant (International Journal of Aquatic Research and Environmental Studies, 2026)
Purpose: The increasing emphasis on sustainability, ethical governance, and stakeholder responsibility has encouraged organizations to adopt value-based management approaches that extend beyond financial performance. This study investigates the impact of Value-Driven Management (VDM) on Sustainable and Ethical Organizational Practices (SEOP) and examines the individual contributions of Ethical Leadership, Spiritual Leadership, Servant Leadership, and Values-Based Organizational Culture. The study is conceptually grounded in contemporary leadership theories and the philosophical principles of the Bhagavad Gita, particularly Dharma (righteous duty), Nishkama Karma (selfless action), and Lokasangraha (collective welfare). Research Methodology: A quantitative research design was adopted using a structured questionnaire administered to 430 employees working in public, private, educational, and non-profit organizations across the National Capital Region (NCR), India. Data were analyzed using SPSS through descriptive statistics, reliability analysis, normality assessment, Pearson’s correlation, simple linear regression, and multiple regression analyses. Value-Driven Management was operationalized through Ethical Leadership, Spiritual Leadership, Servant Leadership, and Values-Based Organizational Culture, while Sustainable and Ethical Organizational Practices comprised Environmental Sustainability, Social Responsibility, Ethical Governance, and Ethical Organizational Climate. Findings: The findings revealed a strong and statistically significant positive relationship between Value-Driven Management and Sustainable and Ethical Organizational Practices. Regression analysis confirmed that Value Driven Management significantly predicts sustainable and ethical organizational outcomes. All four dimensions of Value-Driven Management demonstrated significant positive effects on Sustainable and Ethical Organizational Practices. Among these dimensions, Servant Leadership emerged as the strongest predictor, followed by Values Based Organizational Culture, Ethical Leadership, and Spiritual Leadership. The results further indicated that organizations emphasizing ethical values, responsible leadership, and stakeholder welfare are more likely to achieve higher levels of sustainability, ethical governance, and organizational integrity. Practical Implications: The study highlights the importance of integrating ethical, servant, and spiritual leadership practices into organizational systems and policies. Organizations can enhance sustainability and ethical performance by fostering a values-based culture that promotes accountability, social responsibility, and collective welfare. The findings provide actionable insights for managers, policymakers, and organizational leaders seeking to strengthen ethical excellence and long-term sustainability. Originality/Value: This study contributes to the existing literature by integrating multiple leadership dimensions within a unified Value-Driven Management framework and empirically examining their influence on Sustainable and Ethical Organizational Practices. It further extends the management literature by linking contemporary organizational constructs with the philosophical teachings of the Bhagavad Gita, thereby offering a culturally relevant and theoretically enriched perspective on ethical and sustainable management.
Keywords: Value-Driven Management; Ethical Leadership; Spiritual Leadership; Servant Leadership; Values Based Organizational Culture; Environmental Sustainability; Social Responsibility; Ethical Governance; Ethical Organizational Climate; Bhagavad Gita.